2005
DOI: 10.1118/1.1871372
|View full text |Cite
|
Sign up to set email alerts
|

Brachytherapy needle deflection evaluation and correction

Abstract: In prostate brachytherapy, an 18-gauge needle is used to implant radioactive seeds. This thin needle can be deflected from the preplanned trajectory in the prostate, potentially resulting in a suboptimum dose pattern and at times requiring repeated needle insertion to achieve optimal dosimetry. In this paper, we report on the evaluation of brachytherapy needle deflection and bending in test phantoms and two approaches to overcome the problem. First we tested the relationship between needle deflection and inser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
77
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 119 publications
(82 citation statements)
references
References 19 publications
(22 reference statements)
3
77
0
Order By: Relevance
“…They adopted an industrial serial-link robot for needle manipulation while motorizing a conventional TRUS probe to produce a smooth sagittal sweep in the rectum. They were the first to demonstrate synchronized needle and imaging action (in training phantoms) and their results on needle tracking and seed segmentation were particularly exquisite (Wan et al, 2005). Despite its many excellent qualifications, however, to our knowledge this system has not reached human trials.…”
Section: Introductionmentioning
confidence: 99%
“…They adopted an industrial serial-link robot for needle manipulation while motorizing a conventional TRUS probe to produce a smooth sagittal sweep in the rectum. They were the first to demonstrate synchronized needle and imaging action (in training phantoms) and their results on needle tracking and seed segmentation were particularly exquisite (Wan et al, 2005). Despite its many excellent qualifications, however, to our knowledge this system has not reached human trials.…”
Section: Introductionmentioning
confidence: 99%
“…Three movement rates, shown in Table I, were considered to demonstrate the ability of the system to reach the target over a variety of displacements magnitudes. These rates were chosen such that the total displacement of the target approximately matches that found in soft tissue procedures [17,18,19]. The direction of the movement of the target is controlled in two primary directions.…”
Section: A Target Movement and Locationmentioning
confidence: 99%
“…In our design process, collection and detailed analysis of this in-vivo information were found to be very useful. It was demonstrated that continuous rotation improved targeting accuracy and reduced insertion force [10], whereas partial rotation increased needle placement accuracy [5]. Therefore, we incorporated the provision for needle rotation in the Euclidean system for improving accuracy and seed delivery.…”
Section: Surgery Modulementioning
confidence: 99%
“…In this system, seeds can only be deposited manually. Wei et al [3], [4] and Wan [5] et al developed a robotic system for prostate brachytherapy where they used an industrial robot to position and orient a single hole template through which a needle can be inserted manually. A separate motorized device was developed to rotate the needle and another module used for operating the US probe.…”
Section: Introductionmentioning
confidence: 99%